Study on the mushroom species Agaricus blazei (Murill) - Győri, J. (International Journal of Horticultural Science, 2007)
Nowadays, Agaricus blazei is known all over the world as a mushroom species with unparalleled medicinal properties besides its culinary delights and therefore its regular consumption is recommended in the first place for the prevention of various cancers. For the past decade researchers have been active in the study of its therapeutic properties. Its production started only a decade ago and there are a number of questions yet to be answered. At the moment, the most widespread technique is to grow it using composts similar to those of the button mushroom. In contrast to the common button mushroom, its production differs markedly from that of the button mushroom in that it develops fruiting bodies only in light and requires that the compost temperature be high, around 25 °C, also in the fruiting period and has a much higher need for fresh air. It is also sold in fresh form but mainly as a dried product, in powdered form or as capsules or pills.